Nasal and Hands Carriage Rate of Methicillin-Resistant Staphylococcus aure-us among Health Care Workers at Alwahda Hospital, Derna - Khnfar, Hussain Y. H.; Thaood, Dalal A.; Abdraba, Ilham O. A.; Omran, Intesar N.; Abdeldaim, Guma M. K. (Al-Mukhtar Journal of Sciences, 2019)
Increasing incidence of Methicillin-Resistant Staphylococcus aureus (MRSA) is a well-documented healthcare and community phenomenon of concern to medical and public health communities all over the world. One of the most important sources of MRSA infection in hospitals is health care workers (HCWs) through nasal or hands carriage. The aim of this study is to determine the rate of methicillin-resistant Staphylococcus aureus among HCWs. A cross-sectional study involving 102 HCWs was conducted at Alwahda hospital, Derna. Nasal and hand swabs were collected and cultured on Mannitol Salt Agar. Gram staining was performed on mannitol fermenting colonies. Slide catalase and coagulase were performed to identify S. aureus. An oxacillin and cefoxitin susceptibility test was carried out on Muller Hinton agar using the modified Kirby-Bauer disc diffusion method. Results: out of 102 healthcare workers, 46 (45.1%) carried S. aureus. The rate of methicillin resistance amongst all S. aureus isolates was 47.8 % (22/46) whereas 21.6 % (22/102) of all HCWs were identified as MRSA carriers. Nurses had the highest MRSA carriage with 53%, compared to other HCW. On the other hand, the highest rate of MRSA (75%) was seen in CCU workers followed by workers of pediatric and surgical wards (66%, 62% respectively). The high rate of nasal and hand MRSA carriage among healthcare workers, especially in high-risk wards, indicates the imperfection of infection control measures in our hospitals and the necessity to improve the infection control program.